Seismicity of the Northern Volcanic Zone of Iceland - Einarsson, Páll; Brandsdóttir, Bryndís (Frontiers in Earth Science, 2021)
A half century of monitoring of the Northern Volcanic Zone of Iceland, a branch of the North America – Eurasia plate boundary, shows that the seismicity is very unevenly distributed, both in time and space. The four central volcanoes at the boundary, Þeistareykir, Krafla, Fremrinámar, and Askja, show persistent but very low-level seismicity, spatially coinciding with their high-temperature geothermal systems. On their rift structures, on the other hand, seismicity is almost absent, except during rifting episodes. Krafla went through a rifting episode in 1975-1984 with inflation, interrupted by twenty diking events with extensive rifting, eruptive activity, and intense seismicity along an 80 km long section of the rift. During inflation periods the seismicity was contained within the caldera of the volcano, reflecting the inflation level of the magma chamber. Diking events were marked by seismicity propagating away from the volcano into the fissure swarms to the south or north of the volcano, accompanied by rapid deflation of the caldera magma chamber. These events lasted from one day to three months, and the dike length varied between one and 60 km. The area around the Askja volcano is the only section of the Northern Volcanic Zone that shows persistent moderate seismicity. The largest events are located between fissure swarms of adjacent volcanic systems. Detailed relative locations of hypocenters reveal a system of vertical strike-slip faults, forming a conjugate system consistent with minimum principal stress in the direction of spreading across the plate boundary. A diking event into the lower crust was identified in the adjacent fissure swarm at Upptyppingar in 2007-2008. Four nests of anomalously deep earthquakes (10-34 km) have been identified in the Askja region, apparently associated with movements of magma well below the brittle-ductile transition. Several processes have been pointed out as possible causes of earthquakes in the deformation zone around the plate boundary. These include inflation and deflation of central volcanoes, intrusion of propagating dikes, both laterally and vertically, strike-slip faulting on conjugate fault systems between overlapping fissure swarms, deep migration of magma, and geothermal heat mining.